Endocrine Function, Glucose Homeostasis and After Pancreas Transplantation Insulin Resistance - Hartmann, Marcelo Junges; Bertoluci, Marcello Casaccia; Guterres, Maria Cláudia; Diogo, Luciano Passamini; Saitovitch, David; Gullo Neto, Salvador; Falavigna, Manlio; Kroth, Leonardo Viliano; Traesel, Moacir Alexandre (Brazilian Journal of Transplantation, 2007)
The goal of the pancreatic transplantation is to restore the glucose homeostasis to prevent or improve secondary complications to diabetes and improving the quality of life. Successful transplantations have a good metabolic controlling. These might be or not associated to hyperinsulinemia and increased insulin resistance. HOMA may be useful in evaluating post-transplant beta-cell function.